Determining factors for Cannabis use among Moroccans Schizophrenic Patients: A cross sectional study - Bouri Sara; Zemmama Hanane; El Ayoubi Idrissi Khadija; Berraho Mohamed Amine; Abdellaoui Abdelfattah; Badiaa Lyoussi; Rammouz Ismail; Achour Sanae (Mashhad University of Medical Sciences, 2019)
Objective: Cannabis use is considered a major clinical problem associated with a poorer outcome in patients with schizophrenia. The objective of the present study was to assess the prevalence of cannabis us among patients with schizophrenia. The assessment consists in comparing some factors related to substance use in a population of schizophrenic patients between cannabis users and non-users. Materials and Methods: Four hundred and three participants who were examined prospectively during their hospitalization answered the PANNS scale of schizophrenia, GAF, BIS-10, CDSS, and MARS. The consumption of cannabis was investigated using urine toxicological analysis. Sociodemographic, clinical and therapeutic data were also recorded. Results: The prevalence of cannabis use among schizophrenic inpatients was 49%. Patients with cannabis use were younger (31.7 vs 34.9 years old, p<0.001), more often male (52 vs 20% female, p<0.001), and they presented more often a history of imprisonment (68.8% vs 31.2%, p<0.001). Patients who were users of cannabis had a lower age at onset of the disease than non-users (23.6 vs 24.8 years, p=0.029), and more often with poor medication adherence (p=0.001). Logistic regression revealed that factors associated with cannabis use among schizophrenics were the age, gender, history of imprisonment and poor medication adherence. Conclusion: The study showed that a high prevalence of cannabis use among patients with schizophrenia which was associated with negative overall outcomes. Determining comorbid substance use disorders among schizophrenic patients is crucial as it may contribute to establish a better therapeutic strategy.